1998
DOI: 10.3354/dao032157
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leptodora kindti (Cladocera:Leptodoridae) in the life cycle of Raphidascaris biwakoensis (Nematoda:Anisakidae), a fish parasite in Lake Biwa, Japan

Abstract: NOTERole of Leptodora kindti (Cladocera: Leptodoridae) in the life cycle of Raphidascaris biwakoensis (Nematoda: Anisakidae), a fish parasite in Lake Biwa, Japan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In this trial, the majority of prevalence rates, varying from 30 to 48.8%, were higher than the one verified by De et al (1986) Bashirullah, 1974 than that one observed in this essay (30 to 70.6%). These results showed higher prevalence rates when compared to results of Moravec et al (1998) with Raphidascaris biwakoensis Fujita, 1928.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In this trial, the majority of prevalence rates, varying from 30 to 48.8%, were higher than the one verified by De et al (1986) Bashirullah, 1974 than that one observed in this essay (30 to 70.6%). These results showed higher prevalence rates when compared to results of Moravec et al (1998) with Raphidascaris biwakoensis Fujita, 1928.…”
Section: Resultsmentioning
confidence: 65%
“…Their life cycle has been studied in copepods (Stromberg and Crites, 1974;Bashirullah and Ahmed, 1976;De et al, 1986), amphipods (Moravec, 1996) and cladocerans (Moravec et al, 1998). In laboratory conditions, Campana-Rouget (1961), Stromberg and Crites (1974), Bashirullah and Ahmed (1976) and De et al (1986) studied the infection rate and the life cycle evolution of camallanid larvae in microcrustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…Raphidascaris gigi (syn. R. biwakoensis, R. plecoglossi) is endemic to Lake Biwa, Japan, where it takes the cladoceran Leptodora kindti as a planktonic intermediate host (Moravec et al 1998). As an adult, this nematode inhabits the stomach or intestine of Pelteobagrus nudiceps, Plecoglossus altivelis, Salmo irideus, S. gairdneri, and Oncorhynchus masou (Fujita 1928;Kataoka and Momma 1934;Yamaguti 1935a;Nagasawa 1989, 2002).…”
Section: Affinis Poecilia Latipinna Heterandria Formosa Lucania Gomentioning
confidence: 99%